The Limitations of Bad Prejudice in Social Relations: A Comparison of the Interpretation of Quraish Shihab and al-Thabathaba'i in QS. al-Hujurat:12 - Albab, Muhammad Ulul; Andayani, R. Silvia; Thobroni, Ahmad Yusam (FALASIFA : Jurnal Studi Keislaman, 2025)
The subject matter of this research is how the interpretation of QS. al-Hujurat: 12 regarding the limitations of prejudice. Discussing human is closely related to discussing communication relationships between them. This study aims to analyze the limits of someone is considered to do prejudice. This research is a literature research with a normative approach that is studied comparatively (muqaran), carried out by extracting primary sources of Qur'anic verses and secondary sources that are processed from the opinions of Quraish Shihab and al-Thabathaba'i. The results of the research show that: The primary source of prejudice is the Qur'anic verse. The results of the research show that: 1). Quraish Shihab's interpretation leads that prejudice is not recommended and must be avoided in any form. 2). While al-Thabathaba'i states that prejudice is still allowed as long as it is still in the realm of ideas, because there is no bad impact on others. The similarity between these two interpretations shows the danger of prejudice when it has spread among the community. The emergence of current hoaxes may begin with prejudice against other parties. Thus, good communication needs to be built to avoid prejudice that can destroy the joints of community life.